Painting the Seasons of the Flint Hills - Louis Copt (Symphony in the Flint Hills, 2012)
To truly understand the Flint Hills, they must be experienced in every season–not just the eye-numbing green of spring, but the explosion of the summer wildflowers to the red and golden grasses of fall, and the deep purple and mauve shadows of winter.
Keywords: art; painting; season; summer; fall; winter; spring; green; wildflowers; color; explosion; William Allen White; Flint Hills; Kansas; photography; poem; music; stories; Louis Copt; snow; flowers; animals; beauty; wildlife; nature